Journal of a Trip to California by the Overland Route Across the Plains in 1850-51 - Ingalls, E. S. (Eleazer Stillman), 1820-1879 (Salt Lake City, UT : Project Gutenberg, 2010)
"Journal of a Trip to California by the Overland Route Across the Plains in 1850-51" by E. S. Ingalls is a historical account written in the early 1850s. The narrative chronicles the author$1 (Bs journey from Illinois to California during the westward migration, detailing practical aspects, challenges, and insights experienced along the way. This memoir captures the spirit of adventure and the realities faced by emigrants seeking fortune and a new life in California during the Gold Rush. The opening of the journal introduces Ingalls as he begins his journey from Lake County, Illinois, on March 27. The narrative begins with his travels through familiar locales, meeting fellow travelers, and encountering unexpected tragedies, such as the death of a California emigrant named Maynard. The descriptions of towns, the landscapes he traverses, and the difficulties of the road, including weather challenges and road conditions, set a vivid scene. Ingalls offers candid reflections on his experiences, outlining both the camaraderie among emigrants and the hardships they endure, which includes navigating treacherous terrains and managing scarce resources. (This is an automatically generated summary.)s
Release date is 2010-03-25
E-text prepared by the Project Gutenberg Online Distributed Proofreading Team (http://www.pgdp.net) from digital material generously made available by Internet Archive/American Libraries (http://www.archive.org/details/americana)
Keywords: West (U.S.) -- Description and travel; Overland journeys to the Pacific; Ingalls, E. S. (Eleazer Stillman), 1820-1879; West (U.S.) -- History -- 1848-1860